Boron nitride powder, resin composition, and method for producing boron nitride powder

CN118660861BActive Publication Date: 2026-10-16DENKA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380020357.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-28
Publication Date
2026-10-16
Estimated Expiration
2043-03-28

AI Technical Summary

Benefits of technology

[0026] According to this disclosure, boron nitride powder for improving the long-term insulation properties of thermally conductive insulating materials, a method for manufacturing the same, and a resin composition using the aforementioned boron nitride powder are available.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004978715490000281
    Figure BDA0004978715490000281
Patent Text Reader

Abstract

The present invention relates to a boron nitride powder comprising aggregated particles composed of primary particles of boron nitride, the graphitization index of the aforementioned boron nitride powder being 2.0 or less, the boron oxide content being 0.1 mass% or less, and the boron oxide content after a heat cycle test being 0.2 mass% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to boron nitride powder, resin compositions, and methods for manufacturing boron nitride powder. Background Technology

[0002] Effective heat dissipation during operation is a challenge in electronic components such as power devices, transistors, thyristors, and CPUs. Previous approaches have focused on increasing the thermal conductivity of the insulating layer of printed circuit boards (PCBs) housing electronic components, and mounting electronic components or PCBs to heat sinks using electrically insulating thermal interface materials. For materials requiring both thermal conductivity and insulation (thermally conductive insulating materials), ceramic powders with high thermal conductivity are used.

[0003] As for the aforementioned ceramic powders, boron nitride powder, which possesses properties such as high thermal conductivity, high insulation, and low relative permittivity, has attracted attention. On the other hand, since the thermal conductivity of boron nitride particles (especially hexagonal boron nitride particles) is highly anisotropic, it has been studied to produce boron nitride aggregated particles by aggregating the primary boron nitride particles, thereby suppressing the anisotropy of thermal conductivity caused by the orientation of the primary particles (for example, Patent Document 1).

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-135731 Summary of the Invention

[0007] The problem that the invention aims to solve

[0008] However, in scenarios where electronic components are used for extended periods under high temperature and / or humidity loads, the insulation properties of the thermally conductive insulating materials incorporated into the electronic components (e.g., thermally conductive insulating materials containing boron nitride powder as filler) gradually decrease, potentially leading to insulation failure. Therefore, there is a need for thermally conductive insulating materials that can maintain excellent insulation properties over a long period of time, i.e., thermally conductive insulating materials with excellent long-term insulation properties.

[0009] One aspect of this disclosure is to provide boron nitride powder that improves the long-term insulation properties of thermally conductive insulating materials. Another aspect of this disclosure is to provide a method for manufacturing the aforementioned boron nitride powder. Furthermore, another aspect of this disclosure is to provide a resin composition using the aforementioned boron nitride powder.

[0010] Methods for solving problems

[0011] The inventors of this application discovered through research that the boron oxide (B2O3) content in boron nitride powder affects the insulation properties of thermally conductive insulating materials, and that the boron oxide content in boron nitride powder increases under the operating conditions of the aforementioned electronic components. Based on these insights, the inventors of this application completed this invention.

[0012] This public document provides at least the following [1] to

[11] .

[0013] [1] Boron nitride powder, comprising aggregated particles formed by the aggregation of primary boron nitride particles, wherein the graphitization index of the aforementioned boron nitride powder is 2.0 or less, the boron oxide content is 0.1% by mass or less, and the boron oxide content is 0.2% by mass or less after a thermal cycling test of a total of 1000 cycles with the operation described in (i) as one cycle.

[0014] (i) 10 g of the aforementioned boron nitride powder was heated from 0°C to 50°C at a heating rate of 3.0°C / min under 80% RH conditions, and held for 30 minutes. Then, it was cooled from 50°C to 0°C at a cooling rate of 1.5°C / min and held for 30 minutes.

[0015] [2] The boron nitride powder as described in [1], wherein the crushing strength of the aforementioned aggregated particles is 4 MPa or higher.

[0016] [3] The boron nitride powder as described in [1] or [2] has a water content of less than 300 ppm by mass.

[0017] [4] The boron nitride powder as described in any one of [1] to [3] has a specific surface area of ​​5.0 m². 2 / g or less.

[0018] [5] The boron nitride powder as described in any one of [1] to [4] has an average particle size of 10 to 90 μm.

[0019] [6] The boron nitride powder as described in any one of [1] to [5] has an orientation index of 15 or less.

[0020] [7] A resin composition comprising a resin and boron nitride powder as described in any one of [1] to [6].

[0021] [8] A method for manufacturing boron nitride powder, comprising a decarburization crystallization step, wherein primary boron nitride particles are generated by calcining and cooling a raw material mixture containing boron carbonitride powder and a boron source, and powder containing aggregated particles formed by the aggregation of the aforementioned primary particles is obtained, wherein in the aforementioned decarburization crystallization step, the nitrogen concentration is 99.90% by volume or more and the leakage is 270 × 10⁻⁶. -4 Pa·m 3The aforementioned raw material mixture is calcined and cooled in a closed space of less than / sec.

[0022] [9] The method for manufacturing boron nitride powder as described in [8] further includes, after the aforementioned decarburization and crystallization process, a process of crushing the aggregated particles in the aforementioned powder by friction shearing.

[0023]

[10] The method for manufacturing boron nitride powder as described in [8] or [9] further includes, after the aforementioned decarburization and crystallization step, a step of cleaning the aforementioned powder or its pulverized form.

[0024]

[11] A method for manufacturing boron nitride powder as described in any one of [8] to

[10] , wherein, in the aforementioned decarburization and crystallization process, the temperature is raised from below 1000°C to a holding temperature of above 1900°C at a heating rate of 0.5 to 5.0°C / min, and the holding temperature is maintained for more than 2 hours, thereby calcining the aforementioned raw material mixture.

[0025] Invention Effects

[0026] According to this disclosure, boron nitride powder for improving the long-term insulation properties of thermally conductive insulating materials, a method for manufacturing the same, and a resin composition using the aforementioned boron nitride powder are available. Detailed Implementation

[0027] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. Regarding the content of each component in the composition, if multiple substances are present as components, unless otherwise specified, the content refers to the total amount of those substances present in the composition. In this specification, numerical ranges indicated by "~" represent the ranges containing the minimum and maximum values, respectively. The upper or lower limit of the numerical range described in this specification can also be replaced by the values ​​shown in the examples. Furthermore, the separately stated upper and lower limits can be combined arbitrarily.

[0028] The following describes embodiments of this disclosure. However, these embodiments are merely examples for illustrating this disclosure and are not intended to limit this disclosure to its contents.

[0029] <Boron nitride powder>

[0030] One embodiment of the boron nitride powder includes aggregated particles formed by the aggregation of primary boron nitride particles. In addition to the aggregated particles, the boron nitride powder may also contain primary particles (non-aggregated particles). The primary boron nitride particles may, for example, be flake-like hexagonal boron nitride particles.

[0031] The graphitization index of the aforementioned boron nitride powder is below 2.0. Here, the graphitization index (GI) is an indicator of the degree of crystallinity of graphite (see, for example, J. Thomas et al., J. Am. Chem. Soc. 84, 4619 (1962)). The graphitization index can also be used as an indicator of the crystallinity of boron nitride. The smaller the graphitization index, the higher the crystallinity of boron nitride. Therefore, boron nitride powder containing boron nitride with a small graphitization index (e.g., hexagonal boron nitride) tends to have further reduced impurities and excellent insulation, and also excellent thermal conductivity due to high crystallinity.

[0032] The graphitization index can also be below 1.9, below 1.8, or below 1.7. Boron nitride powder with such a graphitization index tends to have better insulation properties. The graphitization index can be above 1.2, above 1.3, above 1.4, or above 1.5, and can be 1.2–2.0, 1.3–1.9, 1.4–1.8, or 1.5–1.7.

[0033] The graphitization index in this specification is calculated based on the spectrum obtained by measuring the primary particles of boron nitride contained in boron nitride powder (e.g., the primary particles constituting the aforementioned aggregated particles) using powder X-ray diffraction. First, in the X-ray diffraction spectrum, the area values ​​(in arbitrary units) enclosed by the integrated intensity (i.e., each diffraction peak) of each diffraction peak corresponding to the (100), (101), and (102) planes of the primary particles of boron nitride are calculated from the baselines of the diffraction peaks, and are denoted as S100, S101, and S102, respectively. Using the calculated area values, the value of [(S100+S101) / S102] is calculated to determine the graphitization index. More specifically, it is determined using the method described in the embodiments of this specification.

[0034] The boron oxide (B₂O₃) content in the aforementioned boron nitride powder is less than 0.1% by mass, but can also be less than 0.08% by mass, less than 0.06% by mass, less than 0.04% by mass, less than 0.02% by mass, or less than 0.01% by mass. The lower the boron oxide content, the higher the insulation performance. The lower limit of the aforementioned boron oxide content can be 0% by mass, or it can be 0.001% by mass, 0.002% by mass, 0.005% by mass, or 0.01% by mass.

[0035] After a thermal cycling test of a total of 1000 cycles with the operation described in (i) as one cycle, the boron oxide (B2O3) content in the above boron nitride powder is 0.2% by mass or less, or it may be 0.1% by mass or less, 0.05% by mass or less, 0.015% by mass or less, or 0.013% by mass or less.

[0036] (i) 10 g of the aforementioned boron nitride powder was heated from 0°C to 50°C at a heating rate of 3.0°C / min under 80% RH conditions, and held for 30 minutes. Then, it was cooled from 50°C to 0°C at a cooling rate of 1.5°C / min and held for 30 minutes.

[0037] The aforementioned thermal cycling test was conducted under the assumption of prolonged use of boron nitride powder as a filler in a thermally conductive insulating material under the operating environment of electronic components. With conventional boron nitride powders, the boron oxide content increases after the aforementioned thermal cycling test, resulting in a decrease in insulation performance. In contrast, the boron oxide content of the aforementioned boron nitride powder is suppressed to below 0.2% by mass even after the aforementioned thermal cycling test. Therefore, the long-term insulation performance of thermally conductive insulating materials can be improved using the aforementioned boron nitride powder. Hereinafter, boron nitride powder possessing the property of not easily increasing boron oxide content during the aforementioned thermal cycling test will be referred to as boron nitride powder with excellent weather resistance.

[0038] The lower limit of the boron oxide content after the above thermal cycling test can be 0% by mass, or 0.001%, 0.002%, 0.005%, 0.01%, 0.02%, or 0.03% by mass.

[0039] The boron oxide content mentioned above is based on the total mass of boron nitride powder and can be determined by following these steps.

[0040] (1) After drying boron nitride powder at 120°C for 2 hours, accurately weigh 5g of the dried boron nitride powder in a flat weighing tube and mix it with 15ml of methanol (premium reagent) to obtain a mixture.

[0041] (2) The mixture obtained in (1) above is left to stand on a heating plate at 80°C for 1 hour, and then dried in a dryer at 120°C for 1.5 hours to evaporate the methanol and obtain boron nitride powder with boron oxide removed.

[0042] (3) Cool the boron nitride powder obtained in (2) above to room temperature (e.g., 25°C) in a dryer.

[0043] (4) Weigh the mass of the cooled boron nitride powder (unit: g) and calculate the boron oxide content using the following formula.

[0044] Boron oxide content (mass%) = [(mass of boron nitride powder (5g)) - (mass of cooled boron nitride powder)] × 100 / (mass of boron nitride powder (5g))

[0045] For the same reasons mentioned above, a smaller rate of increase in boron oxide content caused by the thermal cycling test ((increase in boron oxide content before and after the thermal cycling test) / (boron oxide content before the thermal cycling test) × 100) is preferred. The rate of increase in boron oxide content can be below 1000%, or below 900%, 800%, 500%, 300%, or 200%. There is no particular limitation on the lower limit of the rate of increase in boron oxide content; it can be 0%, 20%, or 50%.

[0046] The purity of the aforementioned boron nitride powder can be 98.5% by mass or higher, or 99% by mass or higher, or 99.5% by mass or higher, or 99.9% by mass or higher. The upper limit of the purity of the boron nitride powder can be 100% by mass, or 99.9% by mass or 99.5% by mass.

[0047] The purity of boron nitride powder in this specification refers to the value determined by titration as described later. First, the boron nitride powder sample is decomposed using sodium hydroxide. Ammonia is distilled from the decomposition solution using steam distillation and collected in an aqueous boric acid solution. This collected solution is then titrated using a standard sulfuric acid solution. Based on the titration results, the nitrogen (N) content in the sample is calculated. Based on the obtained nitrogen content, the boron nitride content in the sample can be determined using the following formula, and the purity of the boron nitride powder can be calculated. It should be noted that the formula weight of boron nitride is 24.818 g / mol, and the atomic weight of nitrogen is 14.006 g / mol.

[0048] The boron nitride content [mass %] in the sample = the nitrogen atom (N) content [mass %] × 1.772

[0049] The moisture content of the aforementioned boron nitride powder can be below 300 ppm by mass, or below 250 ppm by mass, 200 ppm by mass, or 100 ppm by mass. There is a tendency for boron nitride powder with lower moisture content to exhibit superior weather resistance. Therefore, boron nitride powder with such moisture content tends to further improve the long-term insulation properties of thermally conductive insulating materials. The lower limit for moisture content can be 0 ppm by mass, or 10 ppm by mass, or 20 ppm by mass.

[0050] The aforementioned moisture content is based on the total mass of boron nitride powder and refers to the value measured according to the Karl Fischer method as described in JIS K0068:2001 "Method for Determination of Moisture in Chemical Products". Specifically, firstly, a specified amount of the test sample (boron nitride powder) is collected into an alumina boat that has been refluxed. It is then placed in a furnace preheated to 25°C, and using nitrogen as the carrier gas, the moisture content generated when heated to the test temperature (300°C) is measured using potentiometric titration. The measured value is converted to a unit mass (1g) to determine the moisture content. For example, the "Trace Moisture Analyzer CA-06" (product name) manufactured by Mitsubishi Chemical can be used. For the titration solution, for example, the "Aquamicron AX" (trade name) manufactured by Mitsubishi Chemical can be used as the catholyte, and the "Aquamicron CXU" (trade name) manufactured by Mitsubishi Chemical can be used as the anolyte.

[0051] The average particle size of boron nitride powder can be 10–90 μm. Boron nitride powder with such an average particle size tends to have better weather resistance. Furthermore, by making the average particle size of the boron nitride powder 90 μm or less, a thinner layer can be formed from the resin composition (e.g., a thermally conductive insulating material). Additionally, by making the average particle size of the boron nitride powder 10 μm or more, the thermal conductivity of the resin composition can be further improved. From these perspectives, the average particle size of the boron nitride powder can also be 80 μm or less, or 70 μm or less, or 20 μm or more, or 30 μm or more, or 20–80 μm or 30–70 μm.

[0052] The average particle size in this specification refers to the 50% cumulative particle size (median particle size) in the cumulative particle size distribution on a volume basis. More specifically, it refers to the particle size (D50) at which the cumulative value in the cumulative particle size distribution on a volume basis obtained by laser diffraction scattering for powders reaches 50%. Laser diffraction scattering is performed according to the method described in ISO 13320:2009. For this measurement, a laser diffraction scattering particle size distribution measuring apparatus can be used. For example, the "LS-13 320" (product name) manufactured by BECKMAN COULTER can be used. During the measurement, no homogenization is performed; the measurement is conducted in the presence of aggregated particles.

[0053] The specific surface area of ​​boron nitride powder can be 5.0 m². 2 Below / g, it can also be 4.5m 2 / g or less, 4.0m 2 / g or less, 3.5m 2 / g or less or 3.0m 2Below / g. There is a tendency that the smaller the specific surface area of ​​boron nitride powder, the smoother the surface of the primary boron nitride particles, and the higher the crystallinity, thus the boron nitride powder tends to exhibit superior weather resistance. Therefore, based on boron nitride powder having such a specific surface area, there is a tendency to further improve the long-term insulation properties of thermally conductive insulating materials. Furthermore, if the specific surface area of ​​the boron nitride powder is 5.0 m² / g... 2 When the boron nitride concentration is below a certain level (e.g., g / g), the primary particles become moderately larger, increasing the porosity within the aggregated particles. This allows the resin to easily penetrate the aggregated particles during compounding, further improving the insulation properties of the resin composition (e.g., thermally conductive insulating materials). The specific surface area of ​​the boron nitride powder can be 1.6 m². 2 / g or more, 1.8m 2 / g or more or 2.0m 2 / g or more. Based on boron nitride powder having such a specific surface area, it is possible to suppress the decrease in the density of primary particles in the aggregated particles, and to suppress the decrease in the heat dissipation of resin compositions (e.g., thermally conductive insulating materials) obtained by compounding with resins. From these viewpoints, the specific surface area of ​​boron nitride powder can be 1.6 to 5.0 m². 2 / g, 1.8~4.5m 2 / g or 2.0~4.0m 2 / g. It should be noted that the specific surface area of ​​boron nitride powder can be adjusted, for example, by controlling the grain growth of primary particles during the manufacture of boron nitride powder.

[0054] The specific surface area in this specification refers to the value measured using a specific surface area measuring device according to JIS Z 8830:2013 "Method for determination of specific surface area of ​​powders (solids) based on gas adsorption", and is calculated using the BET single-point method with nitrogen.

[0055] The orientation index of the aforementioned boron nitride powder can be 15 or less, or 12 or less, or 10 or less. If the orientation index of the boron nitride powder is within the above range, even if at least a portion of the aggregated particles disintegrate and the orientation increases during mixing with the resin, large anisotropy in aspects such as heat dissipation of the resin composition can be suppressed. The aforementioned orientation index can be 3 or more, 4 or more, or 6 or more, and can be 3 to 15, 4 to 12, or 6 to 10. The orientation index of the boron nitride powder can be adjusted, for example, by controlling the growth of primary particles during the manufacture of the boron nitride powder.

[0056] The orientation index of boron nitride powder in this specification refers to the value determined by the following method. First, an X-ray diffraction pattern of boron nitride powder is obtained by performing X-ray diffraction measurements on the boron nitride powder. Based on the X-ray diffraction pattern, the peak intensities I(002) and I(100) corresponding to the (002) and (100) planes are obtained. Using the obtained peak intensities, the orientation index [I(002) / I(100)] of the boron nitride powder is calculated. For example, the "ULTIMA-IV" (product name) manufactured by Rigaku Corporation is used as the X-ray diffraction apparatus.

[0057] The crushing strength of the aggregated particles contained in boron nitride powder can be 4 MPa or higher. From the viewpoint of preventing disintegration when mixed with resin, the crushing strength of the aggregated particles contained in boron nitride powder can also be 5 MPa or higher, 8 MPa or higher, or 10 MPa or higher. Generally, if the graphitization index of boron nitride powder is reduced, the internal voids of the aggregated particles increase due to particle growth, and the crushing strength of the aggregated particles decreases. Therefore, it is difficult to achieve a crushing strength of 5 MPa or higher for aggregated particles while keeping the graphitization index of boron nitride powder below 2.0. However, as described later, by designing the firing conditions (e.g., heating rate) in the decarburization crystallization process during the manufacture of boron nitride powder, particle growth can be achieved in a way that prevents the internal voids of the aggregated particles from becoming excessively large, thus balancing a low graphitization index and high crushing strength. The crushing strength of the aggregated particles can be 20 MPa or lower, 15 MPa or lower, or 12 MPa or lower. By setting the crushing strength of the aggregated particles to below 20 MPa, at least a portion of the aggregated particles moderately disintegrates during compounding with the resin, thus easily suppressing the formation of pores. As a result, the obtained resin composition exhibits higher insulation properties. From the above perspective, the crushing strength of the aggregated particles can be, for example, 4–20 MPa, 5–20 MPa, 8–15 MPa, or 10–12 MPa.

[0058] The crushing strength in this specification refers to the value determined according to JIS R 1639-5:2007 "Fine ceramics - Determination of particle characteristics - Part 5: Crushing strength of a single particle". The crushing strength σ (unit: MPa) of one aggregated particle is determined by the dimensionless number α (α = 2.48) varying according to the position within the aggregated particle, the crushing test force P (unit: N), and the particle size d (unit: μm), using the formula σ = α × P / (π × d). 2 The value was calculated by measuring more than 20 aggregated particles and determining the cumulative destruction rate of 63.2%. A micro compression testing machine can be used for this measurement. For example, the "MCT-210" (product name) manufactured by Shimadzu Corporation can be used.

[0059] <Method for manufacturing boron nitride powder>

[0060] One embodiment of the boron nitride powder manufacturing method includes a decarburization crystallization step, in which primary boron nitride particles are generated by calcining and cooling a raw material mixture containing boron carbonitride powder and a boron source, resulting in powder containing aggregated particles formed by the aggregation of these primary particles. In this decarburization crystallization step, the nitrogen concentration is 99.90% by volume or higher and the leakage rate is 270 × 10⁻⁶. -4 Pa·m 3 The above-mentioned raw material mixture is calcined and cooled in a closed space of less than / sec.

[0061] In the decarburization crystallization process, volatile components (such as boron oxide) are generated, so the process is typically carried out in an open space where gases can flow in and out. However, in this embodiment, by performing the sintering and cooling in the decarburization crystallization process within such a closed space, not only can the boron oxide content in the final boron nitride powder be reduced, but also boron nitride powder with excellent weather resistance can be obtained. The reason for obtaining boron nitride powder with excellent weather resistance is not yet clear, but it is believed that this is because, according to the above method, it is easy to obtain boron nitride powder with high crystallinity of primary particles and high purity of hexagonal boron nitride. That is, it is speculated that by increasing the crystallinity of primary particles and the purity of hexagonal boron nitride contained in the boron nitride powder, the increase in boron oxide content under the operating environment is less likely to occur.

[0062] It should be noted that the term "enclosed space" in this specification refers to a space isolated from the external environment to the extent that gas leakage is below the aforementioned upper limit. An enclosed space may not be completely isolated from the external environment (to the extent that gas cannot flow out or in). An enclosed space is typically formed by dividing a portion of the interior of a firing furnace. For example, an enclosed space can be the space within the firing furnace defined by its inner walls, doors, or lids, or it can be the internal space of a container or similar structure independent of the firing furnace. In this embodiment, in order to minimize the impact of volatile components generated during the decarburization and crystallization process, a mechanism for capturing volatile components can be installed within the enclosed space.

[0063] The "leakage rate" in this instruction manual is determined by creating a vacuum in the enclosed space and calculating the pressure change within that space after a specified period of time. Specifically, it can be measured, for example, by following these steps.

[0064] (1) Use a vacuum pump to evacuate the enclosed space. Stop evacuating after the pressure (vacuum degree) in the enclosed space reaches the ultimate vacuum degree.

[0065] (2) The pressure (vacuum degree) in the enclosed space was measured 1 hour after the vacuuming stopped.

[0066] (3) Using the pressure at the point when the vacuuming stops (starting pressure), the pressure obtained in (2) (ending pressure), and the volume in the enclosed space, the leakage amount is calculated by the following formula.

[0067] Leakage (Pa·m) 3 / sec) = [(Ending pressure - Starting pressure) × Volume of the enclosed space] / 3600

[0068] One embodiment of the boron nitride powder manufacturing method may further include a step of preparing boron carbonitride powder used in the aforementioned decarburization crystallization process (preparation step). Additionally, one embodiment of the boron nitride powder manufacturing method may further include a step of pulverizing the aggregated particles in the powder obtained in the decarburization crystallization process (pulverization step). Furthermore, one embodiment of the boron nitride powder manufacturing method may further include a step of cleaning the powder or its pulverized form obtained in the decarburization crystallization process (cleaning step).

[0069] The following describes in detail each step of the manufacturing method of boron nitride powder.

[0070] (Preparation process)

[0071] The preparation process includes, for example, a pressure nitriding process in which boron carbide powder (B4C powder) is sintered under a nitrogen pressure atmosphere. In the pressure nitriding process, the boron carbide in the boron carbide powder is nitrided to obtain a sinter containing boron carbonitride. According to the pressure nitriding process, a sinter containing hexagonal boron carbonitride with high purity can be obtained.

[0072] Boron carbide powder is an aggregate of boron carbide particles. The purity (boron carbide content) of the boron carbide powder can be 96.0% by mass or more, or 98.0% by mass or more. Commercially available boron carbide powder or separately prepared boron carbide powder can be used. For example, boron carbide powder can be obtained by a method including the following steps: mixing boric acid and acetylene black, heating the mixture at 1800–2400°C for 1–10 hours in an inert gas atmosphere to obtain boron carbide blocks; and then pulverizing the obtained boron carbide blocks and appropriately sieving, washing, removing impurities, and drying them to prepare boron carbide powder.

[0073] The firing and cooling processes in the pressurized nitriding process typically involve a leakage rate of 270 × 10⁻⁶. -4 Pa·m 3The process takes place in a closed space for less than one second. The details of the closed space are the same as those for the closed space used in the decarburization and crystallization process for firing and subsequent cooling, so the description is omitted.

[0074] The firing temperature in the pressure nitriding process is preferably higher than that in the decarburization and crystallization process. For example, the firing temperature in the pressure nitriding process can be 1900–2200°C, 2000–2200°C, or 2100–2200°C. By keeping the firing temperature within the above range, the crystallinity of boron carbonitride can be improved, and the proportion of hexagonal boron carbonitride can be increased. The firing time in the pressure nitriding process is not particularly limited, as long as nitriding is sufficiently carried out; for example, it can be 6–30 hours, 8–25 hours, or 10–20 hours.

[0075] The atmosphere pressure in the pressurized nitriding process can be, for example, 0.6–1.0 MPa, 0.7–1.0 MPa, or 0.8–1.0 MPa. By keeping the atmosphere pressure within the above range, manufacturing costs can be suppressed, and the nitriding of boron carbide can be carried out efficiently and thoroughly. It should be noted that the above atmosphere pressure refers to gauge pressure.

[0076] In the pressurized nitriding process, the nitrogen concentration of the pressurized atmosphere can be, for example, 95.00% by volume or more, 98.00% by volume or more, or 99.90% by volume or more. By keeping the nitrogen concentration within the above range, boron carbide nitriding can be carried out under milder conditions. It should be noted that the above nitrogen concentrations are volume concentrations based on standard conditions.

[0077] The calcined material obtained in the pressure nitriding process can be used directly in the decarburization crystallization process, or it can be used in the decarburization crystallization process after appropriate crushing, grading, cleaning, and heat treatment (e.g., oxidation treatment in an oxygen-containing atmosphere). That is, the preparation process may also include crushing, grading, cleaning, and heat treatment (e.g., oxidation treatment in an oxygen-containing atmosphere). The crushing process can be carried out using general crushers or pulverizers such as ball mills, vibratory mills, and jet mills. It should be noted that "crushing" in this specification also includes "crushing".

[0078] (Decarburization crystallization process)

[0079] In the decarburization crystallization process, boron carbonitride powder (B4CN4 powder) can be decarburized and its crystallinity increased by calcining it together with a boron source. As a result, boron nitride powder (BN powder) containing aggregated particles formed by the aggregation of primary boron nitride particles can be obtained. The boron nitride in the boron nitride powder obtained by this method is typically hexagonal boron nitride, containing aggregated particles formed by the aggregation of primary hexagonal boron nitride particles in a scaly pattern.

[0080] Boron carbonitride powder is an aggregate of boron carbonitride particles. The purity (boron carbonitride content) of the boron carbonitride powder can be 98.0% by mass or higher. Commercially available boron carbonitride powder or the boron carbonitride powder prepared in the above-described preparation process can be used. Using boron carbonitride powder with a high proportion of hexagonal boron carbonitride increases the proportion of hexagonal boron carbonitride in the resulting boron nitride powder. Similarly, using boron carbonitride powder obtained through the above-described pressure nitriding process further increases the proportion of hexagonal boron carbonitride in the resulting boron nitride powder.

[0081] Examples of boron sources include boric acid and boron oxide. They can be used alone or in combination of two or more. Using boric acid as a boron source readily promotes the growth of primary particles. The amount of boron source used can be, for example, 25–50% by mass, based on the total mass of the raw material mixture.

[0082] In the decarburization crystallization process, materials other than boron carbonitride powder and boron sources can also be used. For example, carbonates can be used in addition to boron sources. In other words, the raw material mixture can also include carbonates. Examples of carbonates include sodium carbonate, calcium carbonate, and strontium carbonate. They can be used alone or in combination of two or more. If sodium carbonate is used as the carbonate, it is easy to obtain a growth-promoting effect on primary particles. Based on the total mass of the raw material mixture, the amount of carbonate used can be, for example, 1 to 10% by mass.

[0083] From the perspective of easily obtaining boron nitride powder with superior weather resistance, the leakage rate of the enclosed space where firing and cooling occur during the decarburization and crystallization process can also be 250 × 10⁻⁶. -4 Pa·m 3 / sec or less or 200×10 -4 Pa·m 3 The lower limit for leakage in a confined space can be 0 Pa·m³, or less than 0.5 sec. 3 / sec, or 0.1×10 -4 Pa·m 3 / sec or 0.5×10 -4 Pa·m 3 / sec.

[0084] From the viewpoint of easily obtaining boron nitride powder with superior weather resistance, the nitrogen concentration in the aforementioned enclosed space (the nitrogen concentration in the atmosphere during firing) can be 99.95% by volume or higher. There is no particular upper limit to the nitrogen concentration; it can be 100% by volume or 99.99% by volume.

[0085] The atmosphere pressure during firing in the decarburization crystallization process can be 1 kPa or higher, or 2 kPa or higher, or 3 kPa or higher. By setting the atmosphere pressure to 3 kPa or higher, the crystallinity of boron nitride can be further improved, making it easier to obtain boron nitride powder with superior weather resistance. The atmosphere pressure during firing in the decarburization crystallization process can be below 100 kPa, or below 90 kPa, or below 80 kPa. By setting the atmosphere pressure to 80 kPa or lower, the disintegration of aggregated particles can be further suppressed during the decarburization crystallization process. From the above perspective, the atmosphere pressure during firing in the decarburization crystallization process can be 1–100 kPa, 2–90 kPa, or 3–80 kPa. It should be noted that the above atmosphere pressures refer to gauge pressure.

[0086] The firing temperature in the decarburization crystallization process can be above 1900℃ or above 2000℃. By setting the firing temperature above 1900℃, not only can the growth of primary particles proceed sufficiently, but boron nitride powder with excellent weather resistance is also easily obtained. The firing temperature in the decarburization crystallization process can be below 2400℃, below 2200℃, or below 2100℃. By setting the firing temperature below 2400℃, yellowing of the boron nitride powder can be suppressed. Considering the above points, the firing temperature in the decarburization crystallization process can be, for example, 1900–2400℃, 1900–2200℃, or 2000–2100℃. It should be noted that the above firing temperatures refer to the holding temperature during heating (firing). The starting temperature for heating is not particularly limited and can be room temperature (e.g., 25℃). When heating begins at a temperature lower than the holding temperature, the heating rate up to 1000°C can be, for example, 0.5–10.0°C / min, 2.0–10.0°C / min, or 0.5–5.0°C / min, and the heating rate above 1000°C can be, for example, 0.1–5.0°C / min, 0.5–5.0°C / min, or 2.0–4.0°C / min.

[0087] The firing time in the decarburization crystallization process can be 2 hours or more, or 3 hours or more, or 4 hours or more. By setting the firing time to 2 hours or more, not only can the growth of primary particles proceed more fully, but it is also easier to obtain boron nitride powder with excellent weather resistance. The firing time in the decarburization crystallization process can be less than 40 hours, or less than 30 hours, or less than 20 hours. By setting the firing time to less than 40 hours, it is possible to suppress the increase in manufacturing costs. Considering the above points, the firing time in the decarburization crystallization process can be, for example, 4–40 hours, 6–30 hours, or 8–20 hours. It should be noted that the above firing times refer to the holding time at the holding temperature.

[0088] As described above, by changing the firing conditions in the decarburization crystallization process, the graphitization index of boron nitride powder can be reduced, and the crushing strength of the aggregated particles in the boron nitride powder can be further improved. Specifically, if the raw material mixture is fired by heating from a temperature below 1000°C to a holding temperature above 1900°C at a heating rate of 0.5 to 5.0°C / min, and holding at the aforementioned holding temperature for 2 hours or more, boron nitride powder with a graphitization index of 2.0 or less and a crushing strength of aggregated particles of 5 MPa or more can be easily obtained. From the viewpoint of further reducing the graphitization index and further improving the crushing strength, the heating rate can also be set to 1.0 to 5.0°C / min, or 2.0 to 4.0°C / min.

[0089] After firing, the boron nitride powder can be fully cooled within the aforementioned enclosed space. When the enclosed space is opened to the external environment (e.g., the atmosphere), the temperature of the boron nitride powder can be below 40°C.

[0090] (Grinding process)

[0091] In the pulverization process, the aggregated particles in the powder (boron nitride powder) obtained in the aforementioned decarburization and crystallization process are pulverized. The aggregated particles pulverized in the pulverization process are mainly aggregated particles (so-called tertiary particles) formed by the further aggregation of the primary particles (so-called secondary particles) of boron nitride. According to the pulverization process, by pulverizing the aforementioned tertiary particles in the boron nitride powder, the proportion of the aforementioned secondary particles can be increased.

[0092] According to the inventors' research, the pulverization method in the pulverization process also affects the weather resistance of boron nitride powder. Pulverization can be performed using impact-type pulverization methods with general pulverizers or crushers such as pin mills, jet mills, vibratory mills, planetary mills, wet mills, and bead mills. However, it can also be performed using grinding and shearing pulverization methods such as pounders, stone mills, and fedher mills. According to the latter pulverization methods, there is a tendency to obtain boron nitride powder with higher weather resistance. Grinding and shearing pulverization methods can include methods using stone mills and fedher mills capable of continuous pulverization (grinding). In cases where aggregated particles are pulverized by friction shearing, grinding and shearing can also be performed after impact-based or compression-based pulverization.

[0093] (Cleaning process)

[0094] In the cleaning process, the powder (boron nitride powder) or its pulverized form obtained in the decarburization and crystallization process is cleaned. For example, the cleaning process may involve wet treatment by contacting the boron nitride powder or its pulverized form with acid, followed by cleaning until the conductivity of the cleaning solution is below 0.7 mS / m. By implementing such a cleaning process, the boron oxide content in the boron nitride powder can be reduced. It should be noted that "pulverized form" refers to the powder obtained through the above-mentioned pulverization process, or it can be powder obtained through grading or other processes after the pulverization process.

[0095] Wet processing can be performed, for example, by immersing boron nitride powder or its pulverized form in acid and stirring. The acid used in wet processing can be, for example, dilute nitric acid or concentrated nitric acid. Hydrochloric acid, hydrofluoric acid, and sulfuric acid can also be used as acids in wet processing, but using these acids will generate ionic impurities from the acid. On the other hand, using nitric acid easily suppresses the generation of ionic impurities. In wet processing, the contact time with the acid can be, for example, from 10 minutes to 5 hours.

[0096] The cleaning process is performed by contacting boron nitride powder with a cleaning solution. The cleaning solution is typically a water-containing liquid, such as water or deionized water. A mixture of organic solvent and water can also be used. When the cleaning solution contains components other than water, the water content can be 60% by mass or more, based on the total mass of the cleaning solution. The cleaning process can be performed, for example, by mixing and stirring the wet-treated boron nitride powder or its pulverized form with the cleaning solution. The amount of cleaning solution used can be, for example, 100 to 500 parts by mass relative to 100 parts by mass of boron nitride powder (or its pulverized form). The temperature of the cleaning solution can be, for example, 50 to 90°C. The cleaning solution can be stirred using, for example, a mixer, electromagnetic stirrer, or disperser. The stirring time can be, for example, 30 to 180 minutes. The stirring speed can be, for example, 10 to 100 rpm. The cleaning process can also be repeated multiple times. For example, the following series of operations can be repeated: after mixing and stirring boron nitride powder with the cleaning solution, the boron nitride powder is separated from the cleaning solution, and the separated boron nitride powder is mixed again with a new cleaning solution. During the cleaning process, cleaning can be performed until the conductivity of the cleaning solution is below 0.7 mS / m, or until the conductivity of the cleaning solution is below 0.5 mS / m, 0.3 mS / m, or 0.2 mS / m.

[0097] The cleaning process can be performed before the pulverization process, but a higher cleaning effect is more likely to be achieved if the cleaning process is performed after the pulverization process. That is, a higher cleaning effect is more likely to be achieved if the pulverized powder (boron nitride powder) obtained in the decarburization and crystallization process is cleaned.

[0098] Other treatments besides pulverization and washing can also be performed on the boron nitride powder after the decarburization and crystallization process. For example, a classification process can be performed to obtain boron nitride powder with a desired average particle size. The classification process is usually performed after the pulverization process. In addition, for example, if the boron nitride powder contains magnetizable particles, a magnetizable particle removal process can be performed. Magnetizable particle removal is usually performed on slurries containing boron nitride powder or its pulverized form and water (e.g., slurries containing boron nitride powder or its pulverized form after the washing process described above). Specifically, electromagnetic metal removal devices (e.g., electromagnetic iron removal devices) and permanent magnet metal removal devices (e.g., permanent magnet iron removal devices) can be used, for example. The lower limit of the magnetic flux density of the magnetic field applied to the slurry can be, for example, 0.5T or more, 0.6T or more, 1.0T or more, or 1.3T or more. The upper limit of the magnetic flux density of the magnetic field applied to the slurry can be, for example, 1.8T or less, 1.7T or less, or 1.6T or less. The magnetic flux density of the magnetic field applied to the slurry can be adjusted within the above range, for example, it can be 0.5 to 1.8T.

[0099] The above-described method for manufacturing boron nitride powder yields boron nitride powder with excellent weather resistance. More specifically, for example, a boron nitride powder can be obtained that comprises aggregated particles formed by the aggregation of primary boron nitride particles, has a graphitization index of 2.0 or less, a boron oxide content of 0.1% by mass or less, and a boron oxide content of 0.2% by mass or less after the aforementioned thermal cycling test.

[0100] <Resin Composition>

[0101] One embodiment of the resin composition includes the boron nitride powder described in the above embodiments. The resin composition is used, for example, in thermally conductive insulating materials. Examples of thermally conductive insulating materials include insulating layers of printed circuit boards used in electronic components such as power devices, transistors, thyristors, and CPUs, and thermal interface materials.

[0102] As the resin included in the resin composition, known resins used in thermally conductive insulating materials can be used. Examples of resins include liquid crystal polymers, fluoropolymers, silicone resins, silicone rubbers, acrylic resins, polyolefins (polyethylene, etc.), epoxy resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, polyimides, polyamide-imides, polyether-imides, polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, fully aromatic polyesters, polysulfones, polyethersulfones, polycarbonates, maleimide-modified resins, ABS (acrylonitrile-butadiene-styrene) resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins.

[0103] Based on the total volume of the resin composition, the resin content may be, for example, 15% by volume or more, 20% by volume or more, or 30% by volume or more. Based on the total volume of the resin composition, the resin content may be, for example, 60% by volume or less, 50% by volume or less, or 40% by volume or less.

[0104] Based on the total volume of the resin composition, the content of boron nitride powder can be, for example, 30% by volume or more, 40% by volume or more, 50% by volume or more, or 60% by volume or more. Based on the total volume of the resin composition, the content of boron nitride powder can be, for example, 85% by volume or less, 80% by volume or less, or 70% by volume or less.

[0105] In addition to the resin and boron nitride powder, the resin composition may also contain a curing agent for curing the resin. The curing agent can be appropriately selected depending on the type of resin. When the resin is an epoxy resin, examples of curing agents include phenol (Novolac), acid anhydrides, amino compounds, and imidazole compounds. The content of the curing agent relative to 100 parts by weight of the resin may, for example, be 0.5 parts by weight or more, or 1.0 parts by weight or more. The content of the curing agent relative to 100 parts by weight of the resin may, for example, be 15.0 parts by weight or less, or 10.0 parts by weight or less.

[0106] Example

[0107] The contents of this disclosure will be described in more detail with reference to the embodiments and comparative examples, but this disclosure is not limited to the following embodiments.

[0108] It should be noted that the leakage of the enclosed space in the heating furnace used in the following embodiments and comparative examples was measured according to the following steps.

[0109] (1) Use a vacuum pump to evacuate the enclosed space. Stop evacuating after the pressure (vacuum degree) in the enclosed space reaches the ultimate vacuum degree.

[0110] (2) The pressure (vacuum degree) in the enclosed space was measured 1 hour after the vacuuming stopped.

[0111] (3) Using the pressure at the point when the vacuuming stops (starting pressure, 1 Pa), the pressure obtained in (2) (ending pressure), and the volume in the enclosed space, the leakage amount is calculated by the following formula.

[0112] Leakage (Pa·m) 3 / sec) = [(Ending pressure - Starting pressure) × Volume of the enclosed space] / 3600

[0113] <Example 1>

[0114] [Preparation of boron carbide powder]

[0115] Using a Henschel mixer, 100 parts by weight of orthoboric acid manufactured by Nippon Denko Corporation and 35 parts by weight of acetylene black (trade name: HS100L) manufactured by Denka Corporation were mixed. The resulting mixture was filled into a graphite crucible and heated in an electric arc furnace at 2200°C for 6 hours under an argon atmosphere to obtain lumpy boron carbide (B4C). The lumpy material was coarsely pulverized using a jaw crusher to obtain coarse powder. The coarse powder was further pulverized using a ball mill with silicon carbide balls (diameter: 10 mm) to obtain fine powder. The ball milling was carried out at a speed of 25 rpm for 60 minutes. Then, the fine powder was classified using a vibrating sieve with a mesh size of 63 μm to produce boron carbide powder (B4C powder) with an average particle size of 20 μm. The specific surface area of ​​the boron carbide powder is 0.4 m². 2 / g, purity 98% by mass%.

[0116] The average particle size of the boron carbide powder was determined according to ISO 13320:2009 using a laser diffraction scattering particle size distribution measuring apparatus (apparatus name: LS-13 320) manufactured by Beckman Coulter. It should be noted that the boron carbide powder was not homogenized. For the particle size distribution determination, water was used as the solvent for dispersing the boron carbide powder, and hexametaphosphate was used as the dispersant. The refractive index of water was 1.33, and the refractive index of the boron carbide powder was 2.6.

[0117] The purity of boron carbide powder is calculated by the sum of its carbon and boron content. The carbon content is calculated using combustion infrared absorption spectrometry, and the boron content is calculated using ICP emission spectroscopy.

[0118] [Pressure nitriding process]

[0119] The prepared boron carbide powder was placed in a closed space within a carbon resistance heating furnace (leakage rate: 270 × 10⁻⁶). -4 Pa·m 3 The firing process was carried out for 12 hours (per sec). During this time, the firing atmosphere was set to nitrogen (nitrogen concentration: ≥99.99% by volume), the firing temperature was set to 2050℃, and the atmosphere pressure was set to 0.90 MPa. This yielded a fired product (powder) containing boron carbonitride. Analysis of the fired product using powder X-ray diffraction (XRD) confirmed the disappearance of boron carbide and the formation of boron carbonitride.

[0120] [Atmospheric heating process]

[0121] The calcined material obtained in the pressurized nitriding process is filled into a mullite container and heated in a muffle furnace at 700°C for 12 hours in an atmospheric atmosphere.

[0122] [Decarburization and crystallization process]

[0123] Using a Henschel mixer, the calcined product from the above atmospheric heating process, boric acid, and sodium carbonate were mixed to obtain a raw material mixture. Based on the total mass of the raw material mixture, the amount of boric acid used was 35% by mass, and the amount of sodium carbonate used was 5% by mass. Next, the obtained raw material mixture was filled into a boron nitride crucible and dried in a dryer at 200°C for 12 hours. Then, the crucible was removed from the dryer and placed in a closed space within a resistance heating furnace (leakage: 150 × 10⁻⁶). -4 Pa·m 3 After firing for 5 hours (per sec), the atmosphere was cooled to room temperature (25°C) in the enclosed space. At this point, the nitrogen concentration in the firing atmosphere (nitrogen concentration in the enclosed space) was set to 99.95% by volume, the firing temperature was set to 2000°C, and the atmosphere pressure was set to 0.01 MPa. Furthermore, regarding heating to reach the firing temperature, the temperature was increased from room temperature to 1000°C at a rate of 4°C / min, and then from 1000°C to 2000°C at a rate of 2°C / min.

[0124] [Grinding Process]

[0125] The powder obtained in the decarburization and crystallization process (the calcined powder) was pulverized using a non-impact pulverization method. Specifically, the calcined powder was coarsely crushed using a Makino jaw crusher, and then further crushed using a friction shear crusher (a Multi Mill from Grow Engineering), thereby pulverizing the aggregated particles in the powder. The resulting pulverized material was then classified through a 75 μm sieve to obtain boron nitride powder of Example 1, which contains aggregated particles composed of primary particles of hexagonal boron nitride.

[0126] <Example 2>

[0127] Based on the total mass of the raw material mixture, the amount of sodium carbonate used in the decarbonation crystallization process was adjusted to be 0.5% by mass. Otherwise, the boron nitride powder of Example 2 was obtained in the same manner as in Example 1.

[0128] <Example 3>

[0129] After the pulverized material obtained in the pulverization process is classified by passing it through a sieve with a mesh size of 75 μm, the resulting powder is subjected to the following cleaning process. Otherwise, the boron nitride powder of Example 3 is obtained in the same manner as in Example 1.

[0130] [Cleaning Process]

[0131] 40g of the graded powder was added to 400g of dilute nitric acid (nitric acid concentration: 1% by mass) to prepare a solution, which was stirred at room temperature for 60 minutes. The stirred solution was allowed to stand for one hour, and the supernatant was discarded by decantation. Ion-exchanged water was added and stirred for 30 minutes. Then, solid-liquid separation was performed by vacuum filtration, with water changed for washing until the filtrate became neutral. Washing was continued until the conductivity of the final washing solution (water) reached 0.2 mS / m. Once the conductivity of the washing solution was confirmed to be 0.2 mS / m, the solid component obtained through filtration (filter cake) was subjected to the following treatment to remove magnetizable particles.

[0132] First, the above solid components were mixed with ion-exchanged water at 25°C to prepare 10L of an aqueous slurry with a solid component concentration of 30% by mass. Next, the 10L aqueous slurry was added to a 20L resin container. Then, the aqueous slurry in the resin container was stirred at 100 rpm using a stirrer manufactured by YamatoScientific Co., Ltd. (trade name: Labo Stirra LR500B (equipped with a fully PTFE-coated stirring rod with 100mm long blades)). Next, for an electromagnetic separator capable of wet processing, the excitation current of the electromagnetic separator was set such that 10 sheets of wire mesh with a mesh size of 0.5mm were stacked vertically, and the magnetic force of the wire mesh was 14000G (1.4T). Then, a Watson-Marlow tubular pump (trade name: 704U IP55 Washdown) is installed between the resin container containing the stirred water slurry and the electromagnetic separator, causing the water slurry to circulate from bottom to top through the magnetic separation zone of the electromagnetic separator at a flow rate of 0.2 cm / s for 20 minutes. It should be noted that the flow path connecting the resin container and the electromagnetic separator uses a pump with an inner diameter of [missing information - likely a diameter measurement]. The resin hose has a flow path length of 5m. After circulation, the resulting slurry is subjected to solid-liquid separation by vacuum filtration, thereby obtaining a solid component from which magnetizable particles have been removed. After placing the solid component from which magnetizable particles have been removed onto a boron nitride plate, it is heated at 400°C for 30 minutes under a nitrogen atmosphere using a high-temperature dryer to obtain a dried powder. This dried powder is used as the boron nitride powder of Example 3.

[0133] <Example 4>

[0134] The leakage rate of the enclosed space within the resistance heating furnace used in the decarburization crystallization process was changed to 5.5 × 10⁻⁶. - 4 Pa·m 3 / sec, the nitrogen concentration in the firing atmosphere (nitrogen concentration in the enclosed space) is increased to 99.99% by volume, otherwise, the boron nitride powder of Example 4 is obtained in the same manner as in Example 3.

[0135] <Example 5>

[0136] By changing the pulverizing and grading conditions so that the average particle size of the boron carbide powder obtained in [Preparation of boron carbide powder] is 50 μm, boron carbide powder with an average particle size of 50 μm is used in [Pressure Nitriding Process], and the mesh size of the sieve used in the pulverizing process is changed to 150 μm. Otherwise, boron nitride powder of Example 5 is obtained in the same manner as in Example 4.

[0137] <Example 6>

[0138] By changing the pulverizing and grading conditions so that the average particle size of the boron carbide powder obtained in [Preparation of boron carbide powder] is 15 μm, boron carbide powder with an average particle size of 15 μm is used in [Pressure Nitriding Process], and the mesh size of the sieve used in the pulverizing process is changed to 45 μm. Otherwise, the boron nitride powder of Example 6 is obtained in the same manner as in Example 4.

[0139] <Example 7>

[0140] By changing the pulverizing and grading conditions so that the average particle size of the boron carbide powder obtained in [Preparation of boron carbide powder] is 8 μm, using boron carbide powder with an average particle size of 8 μm in [Pressure nitriding process], and changing the mesh size of the sieve used in the pulverizing process to 53 μm, the boron nitride powder of Example 7 was obtained in the same manner as in Example 4.

[0141] <Comparative Example 1>

[0142] In the decarburization and crystallization process, an open-type sintering furnace was used instead of a closed-space resistance heating furnace, and sintering was carried out at atmospheric pressure. In the pulverization process, a high-speed rotary pin mill (impact pulverization method) manufactured by NIPPON COKE was used for pulverization. Otherwise, boron nitride powder of Comparative Example 1 was obtained in the same manner as in Example 1. It should be noted that by continuously supplying nitrogen gas with a nitrogen concentration of 99.9% by volume into the space where the powder was sintered in the open furnace, the sintering atmosphere was made into a nitrogen atmosphere.

[0143] <Comparative Example 2>

[0144] In the pulverization process, the calcined powder was coarsely crushed using a Makino jaw crusher, and then the coarsely crushed powder was further crushed using a friction shear crusher (Multi Mill manufactured by Grow Engineering) to perform pulverization. Otherwise, boron nitride powder of Comparative Example 2 was obtained in the same manner as Comparative Example 1.

[0145] <Comparative Example 3>

[0146] In the decarburization crystallization process, the firing temperature (holding temperature) was changed to 1850°C and the firing time (holding time) was changed to 15 hours. Otherwise, the boron nitride powder of Comparative Example 3 was obtained in the same manner as Comparative Example 1.

[0147] <Physical Property Evaluation>

[0148] For the boron nitride powders obtained in Examples 1-7 and Comparative Examples 1-3, the boron oxide (B2O3) content, graphitization index (GI), orientation index, purity, moisture content, average particle size, specific surface area, and crushing strength before and after the thermal cycling test were measured using the methods described later. The results are shown in Table 1.

[0149] (B2O3 content)

[0150] The boron oxide (B2O3) content in boron nitride powder was determined according to the following steps.

[0151] (1) After drying boron nitride powder at 120°C for 2 hours, accurately weigh 5g of the dried boron nitride powder in a flat weighing tube and mix it with 15ml of methanol (premium reagent) to obtain a mixture.

[0152] (2) The mixture obtained in (1) above is left to stand on a heating plate at 80°C for 1 hour, and then dried in a dryer at 120°C for 1.5 hours to evaporate the methanol and obtain boron nitride powder with boron oxide removed.

[0153] (3) The boron nitride powder obtained in (2) above is cooled to room temperature (25°C) in a desiccator.

[0154] (4) Weigh the mass of the cooled boron nitride powder and calculate the boron oxide content using the following formula.

[0155] Boron oxide content (mass%) = [(mass of boron nitride powder (5g)) - (mass of cooled boron nitride powder)] × 100 / (mass of boron nitride powder (5g))

[0156] The average value obtained from three determinations using this method is taken as the boron oxide (B2O3) content.

[0157] Next, 10g of boron nitride powder was sealed into a zip-locked polyethylene bag, Unipack C-4. The bag containing the boron nitride powder was then placed in a constant temperature and humidity device (Etak Corporation, trade name: FX420N) pre-set to a temperature of 0°C and a humidity of 80%RH, and a thermal cycling test was conducted for a total of 1000 cycles, with the operation described in (i) below as one cycle.

[0158] (I) Heat from 0°C to 50°C at a heating rate of 3.0°C / min, hold for 30 minutes, and then cool from 50°C to 0°C at a cooling rate of 1.5°C / min, hold for 30 minutes.

[0159] The boron oxide (B2O3) content in the boron nitride powder after the above thermal cycling test was determined using the same method as described above.

[0160] (Graphitization Index)

[0161] The graphitization index (GI) of boron nitride powder was calculated based on the results of powder X-ray diffraction. In the obtained X-ray diffraction pattern, the area values ​​(in arbitrary units) enclosed by the integrated intensity (i.e., each diffraction peak) and its baseline corresponding to the (100), (101), and (102) planes of the primary particles of hexagonal boron nitride were calculated and denoted as S100, S101, and S102, respectively. Using the area values ​​thus calculated, the graphitization index was determined based on the following equation (1).

[0162] GI=(S100+S101) / S102…(1)

[0163] (Orientation Index)

[0164] The orientation index of boron nitride powder was determined based on the results of powder X-ray diffraction. First, boron nitride powder was filled into the recess of a glass sample cell with a depth of 0.2 mm, which is attached to an X-ray diffraction apparatus (manufactured by Rigaku Co., Ltd., trade name: ULTIMA-IV). The sample was then pressed using a powder sample forming machine (manufactured by AmenaTech Co., Ltd., trade name: PX700) at a set pressure M, thereby adjusting the sample for measurement. If the surface of the filler pressed by the forming machine was not smooth, it was manually smoothed before measurement. After irradiating the sample with X-rays and performing baseline correction, the peak intensity ratio of the (002) plane to the (100) plane of boron nitride was calculated, and the orientation index [I(002) / I(100)] was determined based on this value.

[0165] (purity)

[0166] The purity of boron nitride powder was determined using the following method. First, the boron nitride powder was decomposed using sodium hydroxide, and ammonia was distilled from the decomposition solution using steam distillation and collected in an aqueous boric acid solution. This collected solution was then titrated using a standard sulfuric acid solution. Based on the titration results, the nitrogen (N) content in the boron nitride powder was calculated. Based on the obtained nitrogen content, the boron nitride content in the boron nitride powder was determined according to equation (2), and the purity of the boron nitride powder was calculated. It should be noted that the formula weight of boron nitride was 24.818 g / mol, and the atomic weight of nitrogen was 14.006 g / mol.

[0167] The content of boron nitride (BN) in the sample [mass%] = the content of nitrogen atoms (N) [mass%] × 1.772…(2)

[0168] (Moisture content)

[0169] According to JIS K 0068:2001 "Method for Determination of Moisture Content in Chemical Products", the moisture content of boron nitride powder was determined based on the Karl Fischer method. Specifically, firstly, a specified amount of the test sample (boron nitride powder) was collected into an alumina boat that had been refluxed and then placed in a furnace that had been preheated to 25°C. Next, using nitrogen as the carrier gas, the moisture content generated when heated to the test temperature (400°C) was determined by potentiometric titration. The moisture content was determined by converting the results to per unit mass (1 g).

[0170] (Average particle size)

[0171] According to ISO 13320:2009, the average particle size of boron nitride powder was determined using a laser diffraction scattering particle size distribution measuring apparatus (apparatus name: LS-13 320) manufactured by Beckman Coulter. It should be noted that the boron nitride powder was not homogenized. For the particle size distribution determination, water was used as the solvent for dispersing the boron nitride powder, and hexametaphosphate was used as the dispersant. The refractive index of water was 1.33, and the refractive index of the boron nitride powder was 1.80.

[0172] (Specific surface area)

[0173] According to JIS Z 8830:2013 "Method for determination of specific surface area of ​​powders (solids) based on gas adsorption", the specific surface area of ​​boron nitride powder was calculated using the BET single-point method with nitrogen. A specific surface area measuring apparatus (device name: Quantasorb) manufactured by Yuasa Ionics Co., Ltd. was used as the specific surface area measuring device. It should be noted that the measurement was performed after the boron nitride powder was dried and degassed at 300°C for 15 minutes.

[0174] (Crushing strength)

[0175] The crushing strength of aggregated particles was determined according to JIS R 1639-5:2007 "Fine ceramics - Methods for determination of particle characteristics - Part 5: Crushing strength of a single particle". A micro-compression testing machine (manufactured by Shimadzu Corporation, product name "MCT-210") was used for the test. It should be noted that the test was performed on 20 or more aggregated particles, and the value was calculated when the cumulative crushing rate was 63.2%.

[0176] <Performance Evaluation>

[0177] (Evaluation of sheet material production)

[0178] Resin compositions were prepared using the boron nitride powders obtained in Examples 1-7 and Comparative Examples 1-3, respectively, and evaluation sheets were made using these resin compositions. Specifically, firstly, a mixture of 100 parts by weight of naphthalene-type epoxy resin (manufactured by DIC Corporation, HP4032) and 10 parts by weight of imidazole compound (manufactured by Shikoku Kasei Corporation, 2E4MZ-CN) as a curing agent was mixed with boron nitride powder to a concentration of 60% by volume to obtain a resin composition. For mixing with the resin, a degassing compound (manufactured by Thinky Corporation) was used. The mixing conditions were set at 1600 rpm for 3 minutes. The obtained resin composition was coated onto a PET film with a thickness of 0.3 mm. Then, the film was heated at 160°C and 50 kgf / cm². 2 Under relatively mild conditions, the resin sheet (evaluation sheet) was heated and pressurized for 50 minutes to produce a 0.3 mm thick sheet.

[0179] (Long-term insulation performance evaluation)

[0180] After subjecting the aforementioned evaluation sheets to a weathering test at 60°C-90%RH for 500 hours, the insulation breakdown voltage of the evaluation sheets after the weathering test was determined. The insulation breakdown voltage was determined according to JIS C 6481-1996 "Test Method for Copper Clad Laminates for Printed Wiring Boards" using a withstand voltage testing machine (manufactured by Kikusui Electronics Industry Co., Ltd., device name: TOS-8650). The result of Comparative Example 1 was set as 1.0, and the obtained insulation breakdown voltage was relatively evaluated.

[0181] (Evaluation of thermal conductivity)

[0182] The thermal conductivity H (unit: W / (m·K)) of the above-mentioned evaluation sheet was measured. Thermal conductivity H is based on thermal diffusivity A (unit: m). 2 / second), density B (unit: kg / m³) 3The values ​​of specific heat capacity C (unit: J / (kg·K)) were calculated based on the formula H = A × B × C. Thermal diffusivity A was determined by processing the evaluation sheet into a length, width, and thickness of 10 mm and using the laser flash method. The measuring apparatus used was a Xenon Flash analyzer (manufactured by NETZSCH, product name: LFA447NanoFlash). Density B was determined using the Archimedes method. Specific heat capacity C was determined using a DSC (manufactured by Rigaku Corporation, product name: ThermoPlusEvoDSC8230). The result of Comparative Example 1 was set to 1.0, and the obtained thermal conductivity was relatively evaluated. It should be noted that all obtained thermal conductivity values ​​were 10 W / mK or higher.

[0183] [Table 1]

[0184]

Claims

1. Boron nitride powder, comprising aggregated particles formed by the aggregation of primary boron nitride particles. The graphitization index of the boron nitride powder is below 2.

0. The boron oxide content is less than 0.1% by mass. After a thermal cycling test consisting of 1000 cycles, with operation (i) as one cycle, the boron oxide content is less than 0.2% by mass. The boron nitride powder has a moisture content of less than 100 ppm by mass. (i) 10g of the boron nitride powder is heated from 0°C to 50°C at a heating rate of 3.0°C / min under 80% RH conditions, and held for 30 minutes. Then it is cooled from 50°C to 0°C at a cooling rate of 1.5°C / min and held for 30 minutes.

2. The boron nitride powder as described in claim 1, wherein, The crushing strength of the aggregated particles is above 4 MPa.

3. The boron nitride powder as described in claim 1 or 2, having a specific surface area of ​​5.0 m². 2 / g or less.

4. The boron nitride powder as described in claim 1 or 2, wherein the average particle size is 10 to 90 μm.

5. The boron nitride powder as described in claim 1 or 2, wherein the orientation index is 15 or less.

6. The boron nitride powder according to claim 1 or 2, wherein the boron oxide content is less than 0.01% by mass. The boron oxide content after the thermal cycling test was less than 0.015% by mass.

7. A resin composition comprising a resin and boron nitride powder according to any one of claims 1 to 6.

8. A method for manufacturing boron nitride powder, comprising a decarburization crystallization step, wherein primary boron nitride particles are generated by calcining and cooling a raw material mixture containing boron carbonitride powder and a boron source, thereby obtaining powder containing aggregated particles formed by the aggregation of the primary particles. In the decarburization crystallization process, the nitrogen concentration is above 99.90% by volume and the leakage is 5.5 × 10⁻⁶. -4 Pa·m 3 The raw material mixture is calcined and cooled in a closed space of less than / sec.

9. The method for manufacturing boron nitride powder as described in claim 8, wherein, Following the decarburization and crystallization process, the process further includes a step of crushing the aggregated particles in the powder by frictional shearing.

10. The method for manufacturing boron nitride powder as described in claim 8 or 9, wherein, Following the decarburization and crystallization process, a process for cleaning the powder or its pulverized form is also included.

11. The method for manufacturing boron nitride powder as described in claim 8 or 9, wherein, In the decarburization and crystallization process, the raw material mixture is heated from a temperature below 1000°C to a holding temperature above 1900°C at a heating rate of 0.5 to 5.0°C / min, and held at the holding temperature for more than 2 hours, thereby calcining the raw material mixture.

Citation Information

Patent Citations

  • Boron nitride aggregated particle, method for producing boron nitride aggregated particle, resin composition containing boron nitride aggregated particle, and molding

    JP2016135731A

  • Aggregate boron nitride particles, boron nitride powder, production method for boron nitride powder, resin composition, and heat dissipation member

    CN112334408A